Base‐ and Radical‐Mediated Regio‐ and Stereoselective Additions of Thiols, Thio‐Sugars, and Thiol‐Containing Peptides to Trisubstituted Activated exo‐Glycals. Issue 20 (9th March 2015) - Richard, Mylène; Didierjean, Claude; Chapleur, Yves; Pellegrini‐Moïse, Nadia
Abstract: A study was performed for the coupling of thiols, thio‐sugars, and thiol‐containing amino acids and peptides with trisubstituted activated anomeric sugar olefins under basic and radical conditions. The hydrothiolation reaction took place in a regio‐ and stereospecific manner and occurred at the anomeric center and mainly from an approach to the less crowded face, that is, opposite to the O‐4 protecting group. Furano‐ and pyranoglycosylidenes were valuable substrates for the base‐mediated coupling with aromatic and primary thiols, which included 6‐thio‐sugars, cysteine derivatives, and glutathione. The success of the radical‐mediated method depended on the thiol partners as well as the nature of the sugar olefins. Neither of the conditions required the protection of the sugar or the cysteine derivatives. Abstract : The hydrothiolation of the trisubstituted double bond of push‐pull exo ‐glycals was performed under radical and basic conditions. This addition reaction took place in a regio‐ and stereospecific manner and provided a strategy for the preparation of tertiary S ‐glycosides and complex neoglycopeptides of interest; EWG = electron‐withdrawing group, P = protecting group, DBU = 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene, and AIBN = azobis(isobutyronitrile).